Establishment of the Muscle-Tendon Junction During Thorax Morphogenesis in Drosophila Requires the Rho-Kinase. - Vega-Macaya, F.; Manieu, C.; Valdivia, M.; Mlodzik, M.; Olguín, P. (Genetics, 2016)
The assembly of the musculoskeletal system in Drosophila relies on the integration of chemical and mechanical signaling between the developing muscles with ectodermal cells specialized as "tendon cells." Mechanical tension generated at the junction of flight muscles and tendon cells of the notum epithelium is required for muscle morphogenesis, and is balanced by the epithelium in order to not deform. We report that Drosophila Rho kinase (DRok) is necessary in tendon cells to assemble stable myotendinous junctions (MTJ), which are required for muscle morphogenesis and survival. In addition, DRok is required in tendon cells to maintain epithelial shape and cell orientation in the notum, independently of chascon (chas). Loss of DRok function in tendon cells results in mis-orientation of tendon cell extensions and abnormal accumulation of Thrombospondin and ?PS-integrin, which may cause abnormal myotendinous junction formation and muscle morphogenesis. This role does not depend exclusively on nonmuscular Myosin-II activation (Myo-II), indicating that other DRok targets are key in this process. We propose that DRok function in tendon cells is key to promote the establishment of MTJ attachment and to balance mechanical tension generated at the MTJ by muscle compaction.